Disability resources in higher education, part 5: 'A little help from my friends'. Issue 10 (June 2018) - Thompson, Tom L.
Abstract : The work of disability resources in higher education is often unseen and not well‐understood. Consider the story below as a way of understanding some key elements of this work and how you can be a friend. My title is in part based on the Beatles' hit song "With a Little Help from My Friends." This story is an analogy of how a person and a campus could experience one another and discover mutual benefits and joy.